2021
DOI: 10.3390/su13063064
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Characteristics of Utilitarian Walking in the Central Areas of the Cities of Bologna and Porto

Abstract: Walking is a mode of transport that offers many environmental and health benefits. Utilitarian walking refers to walking trips undertaken to fulfil routine purposes. The aim of this paper is to examine the extent to which walking is used as a transport mode for short urban trips in the city centers of Bologna and Porto and the barriers preventing utilitarian walking. Based on a questionnaire (n = 1117) administered in the two cities, results indicated that 21% of the individuals travel by foot, while 47% combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 85 publications
1
22
1
Order By: Relevance
“…The walking frequency of older adults in Zhongshan averages 1.42 trips per day, covering 55% of all utilitarian trips. Utilitarian walking refers to walking trips undertaken to fulfill common purposes (e.g., accomplishing errands or getting to work) (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…The walking frequency of older adults in Zhongshan averages 1.42 trips per day, covering 55% of all utilitarian trips. Utilitarian walking refers to walking trips undertaken to fulfill common purposes (e.g., accomplishing errands or getting to work) (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…However, we found that females were more likely to use the apps for finding locations, while males were more likely to use them for collecting useful walking data. This could be explained by the fact that women generally walk more, but for shorter periods of times, because they have more time restrictions than men [56]. Similarly, previous research also suggested that transportation apps were more likely to be used by higher educated people than by their undergraduate counterparts [50,65], showing that the higher the education level, the more such a person is likely to use apps.…”
Section: Discussionmentioning
confidence: 94%
“…Relationships between the variables were confirmed through Chi-square tests, Pearson correlations, and T-tests. These statistical tests have been widely used in transport studies to compare variables and groups [41,55,56]. Chi-square tests were conducted to test associations between individual and geographic variables and the use of PNAs, the reasons for using PNAs, as well as to test associations between the individual and geographic variables and the barriers for not using PNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations